Running : a complete guide - Kupris, Bronnie Storch (Estados Unidos : Dell Publishing Co., 1978)
From starting out to marathon running all the basics of this exhilarating, fast-paced sport! Learn about running techniques. warmup exercises, proper gear, the mental and physical benefits of running, and more!
Why run? Who sholud run When to run The where and wear of running Warmups Running form The actual program Dealing with the elements How to stick with it The big bonus: your trimmer shape Hazards and cures The marathon man (person) A final word
Incluye índice
Keywords: RUNNING -- TECHNIQUES; CARRERAS PEDESTRES